2021
DOI: 10.1021/acs.est.1c02532
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Silver Nasal Spray Leads to Nanoparticle Accumulation in Rat Brain Tissues

Abstract: The use of commercial products containing engineered nanomaterials in realistic scenarios may lead to the accumulation of exogenous particles in brain tissues. In this study, we simulated the use of silver (Ag) nasal spray in humans using Sprague–Dawley rats at 0.04 mg/kg/day. Silver-containing particles were explicitly identified in the rat brain after the administration of nasal sprays containing colloidal Ag or silver ions (Ag+) for 2 weeks using multiple methods. The accumulation of Ag-containing particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The mice received 5 and 20 mg/kg/day nanoscale MOF-74-Zn via intranasal instillation for 14 days. Intranasal infusion is a commonly used route of administration to assess the neurotoxicity of nanoparticles. , These intranasal nanoparticles might be able to translocate into the olfactory bulb via olfactory neurons and accumulate in the brain . The level of zinc in the mouse brain increased significantly after exposure to 5 and 20 mg/kg/day MOF-74-Zn (Figure S2c), demonstrating that MOF-74-Zn nanoparticles were doubtlessly adsorbed into the CNS of the mice.…”
Section: Resultsmentioning
confidence: 99%
“…The mice received 5 and 20 mg/kg/day nanoscale MOF-74-Zn via intranasal instillation for 14 days. Intranasal infusion is a commonly used route of administration to assess the neurotoxicity of nanoparticles. , These intranasal nanoparticles might be able to translocate into the olfactory bulb via olfactory neurons and accumulate in the brain . The level of zinc in the mouse brain increased significantly after exposure to 5 and 20 mg/kg/day MOF-74-Zn (Figure S2c), demonstrating that MOF-74-Zn nanoparticles were doubtlessly adsorbed into the CNS of the mice.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, to further verify the therapeutic effects of Ber, Pal and the combined therapy (Ber/Pal) on neuroinflammation in AD, LPS (250 ng/mL) and Aβ 25-35 (20 μM) were utilized to stimulate microglia for NO and inflammatory cytokine detection (Figure 1A-E). The results showed that Ber and Pal significantly reduced the release of NO and reversed the abnormal inflammatory cytokine levels in microglia stimulated by LPS and Aβ [25][26][27][28][29][30][31][32][33][34][35] . Additionally, to evaluate the feasibility and therapeutic role of codelivery systems of Ber and Pal combined treatment in AD, a Ber and Pal combined treatment group was also included.…”
Section: Anti-inflammatory Function Of Hljdd Components In Vitromentioning
confidence: 94%
“…A LIPID MAPS internal standard cocktail was purchased from Avanti Polar Lipids (Alabaster, USA). Aβ peptide (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) (Aβ 25-35 ) was obtained from Beijing Bosen Biotechnology Co., Ltd. (Beijing, China). The PKH26 fluorescent probe was purchased from Maokangbio (Shanghai, China).…”
Section: Materials and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous studies have been conducted to explore the potential ecotoxicology of large AgNPs in a variety of microorganisms [12,13], algae [14], plants [15], invertebrates [16,17] and vertebrates [18,19], these studies have largely concentrated on the effect on individual organisms, and only a few have described the toxicology of ultra-small AgNCs. The trophic toxicology of AgNCs to the aquatic food chain is a significant issue that warrants further research because several previous studies have shown that nanoparticles, including AgNPs, could potentially accumulate in aquatic ecosystems and eventually cause harm to the "top-level" species [20][21][22].…”
Section: Introductionmentioning
confidence: 99%